Ergonomic hazards associated with small scale mining in southern Africa - Jerie, Steven (International Journal of Pure and Applied Sciences and Technology, 2016)
The aim of this paper is to examine the ergonomic hazards associated with small scale mining in Southern Africa. A number of ergonomic health hazards affect the workers involved in the small scale mining. Many people in Southern Africa are working in the informal mining sector without any guarantee of occupational health and safety. Actual work places in deep level mines present unique challenges to ergonomic interventions. Due to the nature of the ore deposits, narrow gold-bearing reefs, geological constraints and the depth at which mining takes place ( as much as over 3 000m below ground level), mining layouts are primarily aimed at reducing the major cause of fatalities in the mining industry, namely fall of ground. The result is that mining takes place in very restricted places with low ceiling heights and high thermal heat loads and involves a large component of physical work. Ergonomics studies the complex relationship between people, physical and psychological aspects of the work environment and aims at optimizing the comfort, health, safety and efficiency of the miner yet this has not been the case in the mining enterprises of Southern Africa. A number of ergonomic hazards are associated with the mining ventures and these include musculoskeletal disorders and the risk factors involve awkward body posture, manual material handling, repetitive motions, force and vibration. Typical ergonomics-related hazards associated with trackless mining equipment underground include restricted vision, and exposure to whole body vibration, noise and dust. The advantages of applying sound ergonomics principles in small scale mining include enhancing efficiency and eliminating significant occupational safety and health risks.